A Schweidel József-szobor sorsa a két világháború között - Fábián Borbála (2025)
The monuments in the territories annexed by the Treaty of Trianon are often referred to as having been destroyed by the invading Serb/Romanian/Czechs. This is also the case with the Schweidel statue in Zombor, erected in 1905, and the statue of Ferenc Rákóczi II. According to my research, these were removed overnight in January 1920. In the early 1920s, these monuments were located in the yard of the Zombor fire barracks. It was Dr. Lőrinc Fehér, a lawyer from Baja, former mayor of Zombor, who first took the initiative to acquire the statues. The City of Baja, with the help of Dr. György Nikolics, a lawyer from Zombor, made several attempts to purchase the statues. The county of Bács-Bodrog also attempted to acquire the statues. In my paper, I will present these attempts on the basis of the documents of the Baja archives and the contemporary press. Jenő Borsay, the first director of the Baja museum, collected the documents concerning the acquisition of the statues. Jenő Borsay discovered that József Schweidel’s father was buried in Baja. He tried to build up a Schweidel cult in Baja. An interesting chapter in the shared history of the two Bácska towns in the years following 1921 can be seen. The memory of Schweidel’s statue continues to live on in the memory of the people of Zombor, thanks to literature and especially to János Herceg. According to the information that has been discovered, the statues were melted after 1931.
Keywords: Bölcsészettudományok; Történettudomány és régészet